Benign transient hyperphosphatemia; is awareness enough to reduce unnecessary dispatch and costs? (Annals of Medical Research, 2023)
Aim: This study aims to examine the etiology of benign transient hyperphosphatemia (BTH) and the necessity of further investigations in patients with elevated alkaline phosphatase (ALP).Materials and Methods: This study was carried out by retrospectively scanning the files of pediatric cases fewer than five diagnosed with isolated ALP elevation and BTH. They were admitted to our tertiary-care hospital for various reasons in January 2017 and March 2021.Results: A total of 47 cases were included in the study. Twenty-five (53.2%) cases were female, and 22 (46.8%) were male. The cases mainly applied in the summer and autumn seasons (72.4%). The most common age groups were 1 to 2 years (44.7%) and 0 to 1 years old (29.8%). When the laboratory values of the patients were examined, no abnormal values were observed except for ALP elevation. The median ALP value was 2211 (1019-4555) (IU/mL). The median time for ALP to return to normal was 43.5 (15-120) days. When the patients were examined according to the age group, it was observed that the elevation in the ALP level increased as the age decreased, but there was no difference between the median recovery times.Conclusion: Transient ALP elevation is a benign and temporary condition. ALP levels usually return to normal before four months, and ALP levels may persist in sporadic patients. Transient ALP elevation has been associated with many diseases, and it is difficult to attribute its etiology to a precise mechanism. ALP elevation is usually multifactorial